2006
DOI: 10.12968/hmed.2006.67.11.22229
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of the trainees' experience of assessments in the MMC foundation programme

Abstract: The foundation programme for training junior doctors officially started in August 2005, with one key component being assessment of competencies. This qualitative study examined the opinions of foundation programme trainees regarding the perceived use of the assessments for training purposes and where the difficulties lay in completing assessments. Early identification of possible pitfalls should help improve the system for future trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Reports of early pilot schemes in 2003/2004 69 suggested that trainees were generally positive about Foundation but the authors recognized that their participants may have been a highly motivated and therefore atypical group. Other studies have examined the new tools employed in Foundation assessment 1012 and there has been some work on the impact of Foundation in particular specialties. 1315 A UK-wide quantitative study reported some concerns with the F1 year 3 and the Tooke 4 report highlighted some issues with Foundation training as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of early pilot schemes in 2003/2004 69 suggested that trainees were generally positive about Foundation but the authors recognized that their participants may have been a highly motivated and therefore atypical group. Other studies have examined the new tools employed in Foundation assessment 1012 and there has been some work on the impact of Foundation in particular specialties. 1315 A UK-wide quantitative study reported some concerns with the F1 year 3 and the Tooke 4 report highlighted some issues with Foundation training as a whole.…”
Section: Discussionmentioning
confidence: 99%